2008
DOI: 10.1375/twin.11.6.597
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of HbA1c and Fasting Blood Glucose in Different Measurement Settings

Abstract: I n an extended twin study we estimated the heritability of fasting HbA1c and blood glucose levels. Blood glucose was assessed in different settings (at home and in the clinic). We tested whether the genetic factors influencing fasting blood glucose levels overlapped with those influencing HbA1c and whether the same genetic factors were expressed across different settings. Fasting blood glucose was measured at home and during two visits to the clinic in 77 healthy families with same-sex twins and siblings, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 34 publications
3
45
1
Order By: Relevance
“…Design and participants This study used a twin/same-sex sibling design to address the genetic and environmental contribution to the variance of beta cell function in Dutch twin families recruited from the Netherlands Twin Register [24] as described previously [25]. The clamp tests were performed in 125 (58 men) healthy participants, aged 20 to 50 years and of European origin.…”
Section: Methodsmentioning
confidence: 99%
“…Design and participants This study used a twin/same-sex sibling design to address the genetic and environmental contribution to the variance of beta cell function in Dutch twin families recruited from the Netherlands Twin Register [24] as described previously [25]. The clamp tests were performed in 125 (58 men) healthy participants, aged 20 to 50 years and of European origin.…”
Section: Methodsmentioning
confidence: 99%
“…86 Twin and family studies have shown that HbA1c levels are heritable in nondiabetic individuals. 80,91,92 In addition, significant correlation in HbA1c between monozygotic twins both concordant and discordant for type 1 diabetes, 80,93 as well as in siblings with type 1 diabetes, 94,95 suggests that some genetic factors influence HbA1c in individuals with and without diabetes. Studies involving twins showed the substantial contribution of genetic influences to the variance in fasting blood glucose levels as well as in HbA1c levels.…”
Section: Physiological Relationship Between Glucose and Hemoglobinmentioning
confidence: 99%
“…There was a high level of intra-pair agreement on contact frequency for the 4317 pairs in which both twins responded (rho = 0.81). The average level of contact frequency within the pair was used for (Fenger et al, 2007) e (Goode et al,2007) f (Henneman et al, 2008) g (Isaacs et al, 2007) h (McQueen et al, 2003) i (Snieder et al, 1999) j (Souren et al, 2007) k (VelasquezMelendez et al, 2007) l (Chien et al, 2007) m (Iliadou et al,2005) n (Hokanson et al, 2003) o (Beekman et al, 2002) p (Iliadou et al, 2001) q (Middelberg et al, 2002) r (Santos et al, 2006) s (Snieder et al, 2001) t (Simonis-Bik et al, 2008) u (Berrahmoune et al, 2007) v (Fox et al, 2008) w (Lange et al, 2006) x (Su et al, 2008) y (Wessel et al, 2007) z (Worns et al, 2006) https://www. these pairs.…”
Section: Twin Contact and Age At Separationmentioning
confidence: 99%